Muhammadiyah’s Contributions to Education, Social, Cultural, and Political Development: The Perspective of the Nusantara-Middle Eastern Ulama Network - M, Mukhlis; Zulhandra, Zulhandra; Ardianto, Firdaus; Julhadi, Julhadi (Ahlussunnah: Journal of Islamic Education, 2025)
This study analyzes Muhammadiyah’s contributions to educational, social, cultural, and political development in Indonesia through the lens of the Nusantara–Middle Eastern ulama network. Using a qualitative historical-analytical approach, the research examines the intellectual trajectories and transregional scholarly connections of three influential Indonesian Muslim figures: Haji Abdul Malik Karim Amrullah (Buya Hamka), Wahid Hasyim, and Abdurrahman Wahid (Gus Dur). The findings reveal that sustained engagement with Middle Eastern centers of Islamic learning such as Mecca, Medina, Cairo, and Baghdad played a significant role in shaping diverse Islamic orientations in Indonesia, ranging from reformist Muhammadiyah thought to traditionalist and neo-modernist perspectives within Nahdlatul Ulama. Buya Hamka’s modernist outlook contributed to educational reform and socio-cultural transformation through Muhammadiyah. Wahid Hasyim advanced the modernization of pesantren education and strengthened Islamic educational institutions at the state level. Abdurrahman Wahid developed a progressive and pluralistic Islamic vision that reinforced the role of ulama in Indonesia’s socio-political landscape. This study demonstrates that the Nusantara–Middle Eastern ulama network served as a vital conduit for intellectual transmission, enabling Muhammadiyah and related Islamic movements to contribute dynamically to Indonesia’s religious, social, and political development.